Analysis of Factors That Influence The Incidence of Anemia In Teenager at Al Ma’ruf Islamic Boarding School Kediri - Lutfiasari, Dessy; Yanuaringsih, Galuh Pradian (STRADA : Jurnal Ilmiah Kesehatan, 2020)
Fulfilment of optimal balance nutrition will be affected by the health and reproductive system on the teenager. The main problem at that period is an iron deficiency or anaemia. Based on preliminary studies, there were 28 teenagers (29,1%) had anaemia. This research aims to analyze factors that influence the incidence of anaemia in teenager at Al Ma’ruf Islamic Boarding School Kediri. A study design used in this research is correlational analytic with a cross-sectional approach. The population and sample were all teenagers as many as 96 people. The sampling technique used total population. Data analysis using Rho spearman and multiple logistic regression. The result showed factor that influenced the incident of anaemia are age ( 0,017; OR = 7,118), knowledge of nutrition ( 0,006; OR = 0,230), nutritional status (0,000 ; OR = 0,025). Physical activity ( 0,604) and length of menstruation ( 0,071) are not correlated with anaemia.